A qualitative study of community perception and acceptance of biological larviciding for malaria mosquito control in rural Burkina Faso - Dambach, Peter; Mendes Jorge, Margarida; Traoré, Issouf; Phalkey, Revati; Sawadogo, Hélène; Zabré, Pascal; Kagoné, Moubassira; Sié, Ali; Sauerborn, Rainer; Becker, Norbert; Beiersmann, Claudia (BioMed Central, 2018)
Background: Vector and malaria parasite’s rising resistance against pyrethroid-impregnated bed nets and antimalarial drugs highlight the need for additional control measures. Larviciding against malaria vectors is experiencing a renaissance with the availability of environmentally friendly and target species-specific larvicides. In this study,we analyse the perception and acceptability of spraying surface water collections with the biological larvicide Bacillus thuringiensis israelensis in a single health district in Burkina Faso. Methods: A total of 12focus group discussions and 12key informant interviews were performed in 10 rural villages provided with coverage of various larvicide treatments (all breeding sites treated, the most productive breeding sites treated, and untreated control). Results: Respondents’ knowledge about the major risk factors for malaria transmission was generally good. Most interviewees stated they performed personal protective measures against vector mosquitoes including the use of bed nets and sometimes mosquito coils and traditional repellents. The acceptance of larviciding in and around the villages was high and the majority of respondents reported a relief in mosquito nuisance and malarial episodes. There was high interest in the project and demand for future continuation. Conclusion: This study showed that larviciding interventions received positive resonance from the population. People showed a willingness to be involved and financially support the program. The positive environment with high acceptance for larviciding programs would facilitate routine implementation. An essential factor for the future success of such programs would be inclusion in regional or national malaria control guidelines.